1995
DOI: 10.1152/ajplung.1995.269.1.l52
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and reoxygenation stimulate biphasic changes in endothelial monolayer permeability

Abstract: Incubation of bovine pulmonary microvascular endothelial (BPMVE) cells in low O2 content (95% N2-5% CO2) for 4 h increased monolayer permeability to dextran almost twofold and also increased the incidence of intercellular gaps and intracellular actin stress fibers. Hypoxic incubation decreased the extracellular matrix contents of fibronectin and vitronectin, proteins that serve as anchorage points for the endothelial cells. This state was reversed after 24 h of hypoxic incubation, and the BPMVE monolayer perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Many published papers report that acute hypoxia increases endothelial monolayer permeability (11,12,19) and may do so in part through activation of Rho/Rho kinase (11,13). Our preliminary data demonstrate that PMVEC grown to confluence in hypoxia have decreased monolayer permeability, however.…”
Section: Decreased Rho/rho Kinase Activation In Pmvec Grown To Conflumentioning
confidence: 49%
See 2 more Smart Citations
“…Many published papers report that acute hypoxia increases endothelial monolayer permeability (11,12,19) and may do so in part through activation of Rho/Rho kinase (11,13). Our preliminary data demonstrate that PMVEC grown to confluence in hypoxia have decreased monolayer permeability, however.…”
Section: Decreased Rho/rho Kinase Activation In Pmvec Grown To Conflumentioning
confidence: 49%
“…In 1995, Catherine Partridge demonstrated that the permeability of a confluent monolayer of (bovine pulmonary artery) endothelial cells increased within the first 4 to 6 hours after exposure to hypoxia (3% oxygen), although by 24 hours, the permeability of the monolayer had actually decreased relative to baseline (12). More recent studies have also demonstrated an increase in monolayer permeability in cells exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMNendothelial cells interaction (12) and the release of proinflammatory cytokines such as tumor necrosis alpha (TNF-a) and interleukin-1 (IL-1) amplify inflammatory cell recruitment, extravasation and favor vascular permeability alteration and tissue edema (13)(14)(15). While neutrophil transendothelial migration and its pathological consequences are well documented (16)(17)(18), significantly less is known of the mechanisms by which inflammatory cells cross or degrade (19) the basement membrane and infiltrate the surrounding extracellular matrix (ECM) (20).…”
Section: Introductionmentioning
confidence: 99%
“…Signaling pathways that are activated by hypoxia such as p38 mitogen-activate protein (MAP) kinase and Rho kinase pathways alter the actin cytoskeleton and contractile proteins leading to changes in biomechanical forces in these cells (3). These forces likely play an important role in endothelial cell migration and interaction with leukocytes as well as in regulation of endothelial barrier permeability which is altered in hypoxia (10,14,19). Intermediate filaments constitute one of the three major components of the cytoskeleton which also include actin microfilaments and tubulin microtubules.…”
mentioning
confidence: 99%